2021
DOI: 10.3390/antiox10040603
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Targets Metabolism in Head and Neck Cancer Cells by Regulating Mitochondrial Structure and Function

Abstract: Metabolic reprogramming, which is characteristic of cancer cells that rapidly adapt to the hypoxic microenvironment and is crucial for tumor growth and metastasis, is recognized as one of the major mechanisms underlying therapeutic resistance. Mitochondria, which are directly involved in metabolic reprogramming, are used to design novel mitochondria-targeted anticancer agents. Despite being targeted by melatonin, the functional role of mitochondria in melatonin’s oncostatic activity remains unclear. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 53 publications
4
47
1
Order By: Relevance
“…Other previous studies reported that Mel prevents mitochondrial damage and reduces mitochondrial ROS level in various diseases caused by oxidative stress. 51,52 On the contrary, a study by Guerra-Librero et al 53 proposed that Mel induces mitochondrial respiration and glycolytic capacity, resulting in the increase in mitochondrial ROS level and cell death in HNSCCs. Consistent with the study, our results showed that Mel caused a substantial increase in mitochondrial ROS level, which is known to induce apoptosis, cell cycle arrest, and senescence in cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Other previous studies reported that Mel prevents mitochondrial damage and reduces mitochondrial ROS level in various diseases caused by oxidative stress. 51,52 On the contrary, a study by Guerra-Librero et al 53 proposed that Mel induces mitochondrial respiration and glycolytic capacity, resulting in the increase in mitochondrial ROS level and cell death in HNSCCs. Consistent with the study, our results showed that Mel caused a substantial increase in mitochondrial ROS level, which is known to induce apoptosis, cell cycle arrest, and senescence in cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Last but not least, melatonin affected cancer metabolism in Cal-27 and SCC-9 head and neck squamous cell carcinoma (HNCC) cells by regulating mitochondrial function and structure. Melatonin stimulated OXPHOS and suppressed cytosolic aerobic glycolysis leading to ROS production, mitophagy, apoptosis and reduction of cell proliferation [ 113 ].…”
Section: Structural and Functional Aspects Of Melatoninmentioning
confidence: 99%
“…Studies have also shown that glucose metabolism plays an important role in the occurrence and development of HNSCC. For example, metformin is associated with the prevention of HNSCC (42,43). Some important metabolic pathways in our study were tryptophan metabolism, primary bile acid biosynthesis, alpha linoleic acid metabolism, and N-glycan biosynthesis.…”
Section: Discussionmentioning
confidence: 80%